Wound healing: cellular mechanisms and pathological outcomes - Wilkinson, Holly N. (Open Biol, 2020)
Wound healing is a complex, dynamic process supported by a myriad of cellular events that must be tightly coordinated to efficiently repair damaged tissue. Derangement in wound-linked cellular behaviours, as occurs with diabetes and ageing, can lead to healing impairment and the formation of chronic, non-healing wounds. These wounds are a significant socioeconomic burden due to their high prevalence and recurrence. Thus, there is an urgent requirement for the improved biological and clinical understanding of the mechanisms that underpin wound repair. Here, we review the cellular basis of tissue repair and discuss how current and emerging understanding of wound pathology could inform future development of efficacious wound therapies.